PEMANASAN GLOBAL DAN PELAKSANAAN MEKANISME PEMBANGUNAN BERSIH SEKTOR ENERGI DI INDONESIA - Febijanto, Irhan (BPPT)
At this time global warming became an environmental issue that most often discussed. At the same time, as a trigger of green house gasses business, the issue of carbon trading business became an interesting discussion, because it has an impact to improve the feasibility of the project. This paper discussed the causes of global warming, the mechanism of global warming and the efforts to reduce green house gasses using Clean Development Mechanism. In addition, carbon price fl uctuation and the procedures of carbon trading are described also. Finally, potentialClean Development Mechanism projects in energy sector and implemented Clean Development Mechanism projects in Indonesia are discussed.Key Words : Global warming, Clean Development Mechanism (CDM), CDM project, Certified Emission Reduction (CER), Carbon Trading